Working With Interpreters: Learning to Conduct a Cross-Language Medical Interview With an Online Web-Based Module (Out of Print) - Sarah Waldman; Adina Kalet (Association of American Medical Colleges, 2007)
Abstract Studies suggest that the use of culturally appropriate communication in patient encounters leads to greater patient and provider satisfaction, and improved health outcomes. To address this, we created this web-based curriculum to introduce medical students, residents, and practicing health care professionals to the skills, knowledge, and attitudes necessary for working with limited English proficient (LEP) patients through interpreters. Seventy-one percent (n = 456) of first-year students who completed the module consented to having their data included in this evaluation. Mean knowledge scores (19 items) improved from 46% premodule to 62% postmodule, reflecting improvements in knowledge of best interpreter practices, immigration demographics, and legal issues. Mean scores on four of the five attitude items also improved, reflecting attitudes more consistent with the culturally sensitive care required for working with LEP patients. Mean satisfaction with the educational value of the module for 155 students who completed the postmodule survey was 2.9 on a scale of 1 to 4. The interactive format of this module allowed students to receive immediate formative feedback and become cognizant of both the challenges and effective strategies in language-discordant medical encounters.